The Cosmopolitanism of The Table: Commensality, Conviviality, and Intra Muslim Diversity in Kuala Lumpur's Communal Iftar - Suroyo; Derinta Entas; Bima Maulana Putra; Rina Kurniawati; Afrilia Elizabet Sagala; Joachim Baaden (Balai Penelitian dan Pengembangan Agama Jakarta, 2026)
Communal iftar meals during Ramadan are often analysed as a homogeneous in-group practice, yet this overlooks their role as spaces for encounters across the internal diversity of the Muslim world in pluralistic cities. This article examines joint iftar meals in Kuala Lumpur—where diverse traditions converge—as a case of intra-Muslim conviviality. Through a qualitative ethnographic design (observation, interviews and document analysis), this study explores how communal religious meals foster cross-cultural cohesion and what underpins this, by analysing these practices through the sociology of commensality (Simmel, Fischler), theories of ritual interaction and solidarity (Collins, Durkheim), and the literature on urban and multicultural conviviality (Amin, Gilroy). The cohesion of communal iftar depends on institutional infrastructure, the layout of the dining area, and the food served as a medium for exchange. Differences are negotiated through commensality, giving rise to a sense of togetherness that extends from ritual spaces into the public sphere. The hospitality of the mosque, as an infrastructure of intra-Muslim conviviality, shapes a vernacular cosmopolitanism at the table, whilst simultaneously revealing its boundaries—who is welcomed and who remains on the margins of urban Islamic social life.